Synthesis and Optical Characterization of Nd3+ doped TeO2-PbO-Li2O - M. Rahim Sahar; A. Kassim; R Arifin (Universitas Negeri Semarang, 2011)
Glass based on Nd3+-doped TeO2-PbO-Li2O has successfully been made by melt quenching technique and their thermal parameters have been determined using Differential Thermal Analyzer (DTA). The glass is then nucleated and/or growth by controlled heat treatment at slightly below the crystallization temperature. The X-ray diffraction (XRD) technique is used to estimate the nano-crystallite size. Meanwhile, the optical characterization has been determined using the Photoluminescence Spectroscopy. It is found out that the crystallite size is about 20 nm and very much depending on the heat-treatment time. Meanwhile, the intensity of the luminescence spectra is very much depending on the concentration of the dopant. Â Keyword: tellurium glasses, melt quenching technique, optical characterization